2017
DOI: 10.4103/1658-354x.203027
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between intravenous lidocaine and ketamine on acute and chronic pain after open nephrectomy: A prospective, double-blind, randomized, placebo-controlled study

Abstract: Background:Recently, there has been increasing interest in the use of analgesic adjuncts such as intravenous (IV) ketamine and lidocaine.Objectives:To compare the effects of perioperative IV lidocaine and ketamine on morphine requirements, pain scores, quality of recovery, and chronic pain after open nephrectomy.Study Design:A prospective, randomized, placebo-controlled, double-blind trial.Settings:The study was conducted in Charles Nicolle University Hospital of Tunis.Methods:Sixty patients were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
(56 reference statements)
0
36
0
1
Order By: Relevance
“…Although data supporting the use of intravenous lidocaine for treatment of cancer pain are limited, case reports and smaller studies have been published that support its use for opioid-refractory cancer pain or postsurgical pain. [131][132][133][134] One phase 2, randomized, double-blind crossover study of 50 patients with opioid-refractory cancer pain found that pain relief was better with intravenous lidocaine compared with placebo (P,.001). Additionally, more patients were able to decrease their analgesic requirements after administration of intravenous lidocaine than placebo (P5.0012).…”
Section: Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…Although data supporting the use of intravenous lidocaine for treatment of cancer pain are limited, case reports and smaller studies have been published that support its use for opioid-refractory cancer pain or postsurgical pain. [131][132][133][134] One phase 2, randomized, double-blind crossover study of 50 patients with opioid-refractory cancer pain found that pain relief was better with intravenous lidocaine compared with placebo (P,.001). Additionally, more patients were able to decrease their analgesic requirements after administration of intravenous lidocaine than placebo (P5.0012).…”
Section: Ketaminementioning
confidence: 99%
“…133 Some reports suggest that intravenous lidocaine may be especially useful for cancer-related neuropathic pain. [132][133][134] Selecting a Route of Administration for Opioid Analgesics and Mixed Mechanism Drugs The least invasive, easiest, and safest route of opioid administration should be provided to ensure adequate analgesia.…”
Section: Ketaminementioning
confidence: 99%
“…Recent studies report that perioperative infusion of lidocaine may also have an analgesic effect by affecting postoperative serum concentrations of endocannabinoids, N-acylethanolamines (NAE) and endogenous opioids: β-endorphin, enkephalin and dynorphin [28,29]. Numerous studies and meta-analyzes have shown a positive effect of the perioperative systemic lidocaine administration in adults on the postoperative analgesia, gastrointestinal recovery and duration of hospitalization in major surgery [9,10,13,17,21,30]. However recent meta-analyzes suggest that lidocaine exerts a positive analgesic effect only in abdominal surgery [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that lidocaine also beneficially supplements therapy aiming at improving patient comfort in the postoperative period [9][10][11][12][13][14][15][16][17]. However, there are no studies evaluating the intravenous (i.v) lidocaine as an element of analgesic multimodal therapy in spine surgery in children.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study showed that although lidocaine may give rise to a mean reduction of 0.8 to 0.3 in VAS at 1 to 4 hours and 24 hours, no difference could be expected after 24 hours of surgery (7). Lidocaine is shown to also be effective after open surgery as well as tonsillectomy, arthroplasty, coronary artery bypass surgery, supratentorial tumor surgery, and nephrectomy; nevertheless, well-documented detailed evidence has not been reported on its effect after laparoscopic surgery (17)(18)(19)(20)(21). Furthermore, there have been studies, such as that by Gregory L Bryson showing no effect for lidocaine infusion on postoperative pain (5).…”
Section: Discussionmentioning
confidence: 99%